Development and evaluation of microsatellite markers for a native prairie perennial, Echinacea angustifolia (Asteraceae)1. (7th November 2013) - Ison, Jennifer L.; Wagenius, Stuart; Reitz, Diedre; Ashley, Mary V.
Abstract : Premise of the study: Microsatellite loci for the native prairie perennial Echinacea angustifolia were developed and evaluated for future use in population structure and paternity studies. Methods and Results: A total of 50 trinucleotide microsatellite regions were identified though an enrichment protocol that prescreens for microsatellite repeats before ligating into a vector. Of these, 11 loci were polymorphic and in Hardy–Weinberg equilibrium in three populations with varying numbers of plants. The loci had between three and 14 alleles and collectively provided high paternity exclusion probabilities. Conclusions: These sets of microsatellite primers will provide researchers and land managers with valuable information on the population genetic structure and gene flow between fragmented prairie populations.